Opedipal God: The Chinese Nezha and his Indian Origins, by Meir Shahar - Collins, Brian (Religions of South Asia, 2018)
Opedipal God: The Chinese Nezha and his Indian Origins, by Meir Shahar. Honolulu: University of Hawai’i Press, 2015. 312 pp., £49.95 (hb). ISBN 9-780-824-847609.